Wet Feeding Promotes Growth without Affecting Hypothalamic Peptide Gene Expression in Growing Broiler Chicks - Tomoya Matsunami; Yuhui Zhang; Yuji Taniguchi; Sei-ichi Hinomoto; Takaoki Saneyasu; Hiroshi Kamisoyama; Kazuhisa Honda (The Journal of Poultry Science)
From the perspective of animal welfare, freedom from hunger and thirst is an undeniable requirement for the poultry industry. Regulatory mechanisms underlying drinking behavior have not yet been identified in chickens; however, the regulation of osmolality and water intake appears to be closely related. This study clarified whether wet feeding affects appetite, osmolality, and stress-related gene expression in the hypothalami of chicks. In Experiment 1, the effects of different wet feed percentages on the growth of broiler chicks were examined. Wet feeds were prepared by mixing either 0.25 g (20% wet feed), 0.667 g (40% wet feed), or 1.5 g (60% wet feed) of distilled water per g of commercial feed. Then, the wet feeds were offered to 4-day-old broiler chicks until 42 d of age. Forty percent wet feed significantly increased body, breast, and leg weights. In Experiment 2, 7-day-old broiler chicks were given either commercial starter feed or 40% wet feed until 21 d of age. Again, weights of the body, breasts, and legs were significantly increased by wet feeding. The total amount of water loss in the individual waterers was significantly decreased by wet feeding. No significant changes were observed in mRNA levels of the genes encoding appetite-regulatory peptides (neuropeptide Y and α melanocyte-stimulating hormone), osmoregulatory peptides (vasotocin and mesotocin), or stress-related peptides (corticotrophin-releasing factor) in the chicken hypothalamus. Overall, 40% wet feed improved growth without inducing thirst or hunger in broiler chicks. These findings suggest that wet feeding contributes to both meat yield and animal welfare during broiler production.